The business of time : A global history of the watch industry - Donze, Pierre-Yves (Studies in design and material culture., 2022)
World watch production today is concentrated in three countries: Switzerland, Japan and China. Former centres such as Great Britain, France, the United States and Russia saw the industrial manufacture of watches disappear from their territory during the twentieth century. How did this situation come about? The business of time aims to answer this question by presenting the first comprehensive history of the sector. It traces the evolution and transformation of the global watch industry from the mid-nineteenth century to the present day, highlighting the conditions that enabled watch production to expand across the globe and revealing how multinational companies gradually emerged to dominate the industry.